2004
DOI: 10.1097/00008469-200412000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits and lung cancer risk among non-smoking women

Abstract: A case-control study was conducted to investigate the relationship between diet and the risk of lung cancer among women non-smokers and to compare with women smokers in the same population. Data collected by personal interviews from 435 microscopically confirmed cases and 1710 controls were analysed using unconditional logistic regression. In addition to results for all study subjects, associations between diet and lung cancer risk were compared between two highly contrasting groups: smokers (odds ratio (OR) 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…In some recent studies, a protective effect of tea consumption against lung cancer was only observed in specific subpopulations. For example, green tea was protective in individuals with the OGG1 Cys (326) allele [70] and nonsmoking women [71], and black tea in nonsmoking women [72,73]. These results point out the importance of considering genetic polymorphism and specific risk factors in future studies.…”
Section: Lung Cancermentioning
confidence: 82%
“…In some recent studies, a protective effect of tea consumption against lung cancer was only observed in specific subpopulations. For example, green tea was protective in individuals with the OGG1 Cys (326) allele [70] and nonsmoking women [71], and black tea in nonsmoking women [72,73]. These results point out the importance of considering genetic polymorphism and specific risk factors in future studies.…”
Section: Lung Cancermentioning
confidence: 82%
“…This is also the conclusion of a recent review, which covers 14 epidemiological studies on green and black tea consumption and lung cancer risk (Clark and You, 2006). In some recent studies, a protective effect of tea consumption against lung cancer was only observed in special subpopulations; for example, green tea in individuals with the Cys(326) allele of 8-oxoguanine-DNA glycosylase (Bonner et al, 2005) and nonsmoking women (Zhong et al, 2001), and black tea in nonsmoking women (Kubik et al, 2004). The results are interesting, but are far from clear because of the many confounding factors.…”
Section: Human Studiesmentioning
confidence: 86%
“…Among women, consumption of milk may decrease risk of colorectal cancer (1) and cervical cancer (2), but have no effect on breast cancer e.g., (3)-4) or endometrial cancer (4). Results for lung cancer are quite mixed, with some studies suggesting risk reduction e.g., (5) or risk enhancement e.g., (6) that may vary by gender (7) or the histology of the tumor (8). A recent review on ovarian cancer concluded that consumption of low-fat milk is protective (9), but a pooled analysis of 12 cohort studies observed an elevated risk associated with increased lactose intake (10).…”
Section: Introductionmentioning
confidence: 99%